ANALYSIS OF IMPLEMENTATION OF MARKETING STRATEGY IN MUSLIMAH SWIMMING POOLS IN ARCAMANIK, BANDUNG CITY - Fitri Mulyani; Imelda Putri; Liza Muthainah Kheriyah (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2020)
The development of Islamic swimming pools in Indonesia has a positive trend. Several cities in Indonesia have established Islamic swimming pools. Including in Bandung there is a sharia swimming pool called the Muslimah Arcamanik Swimming Pool. Located in a strategic location. The swimming pool at Arcamanik has facilities that meet the needs of visitors but the number of visitors is not maximized. This type of research uses descriptive qualitative research. Data collection was carried out by observation, interview and documentation. The selection of informants in this study used a sampling technique. The research sample consisted of three people, namely managers, employees, and visitors. The results of the analysis show that the Arcamanik Muslimah swimming pool is not much different from a public swimming pool, it is open to all groups, both Muslims and non-Muslims. What distinguishes only the swimming pool where the Muslimah Arcamanik swimming pool does not accept male visitors.